Black people's racial identity and their acceptance of Black-White Multiracial people. (December 2019) - Franco, Marisa; Holmes, Olivia L.; Swafford, Felicia; Krueger, Nolan; Rice, Kenneth
The current study examined whether Black people's racial ideology, experiences of racism, and their interaction predict their acceptance of Black-White Multiracial people. Black racial ideologies represent an aspect of Black people's racial identity that addresses their perspectives on how people within the Black community should behave. Participants ( N = 325) were administered a series of measures. Latent class analysis revealed three classes of Black racial identity: undifferentiated (average ideologies), integrationist (high assimilationist, humanist, and oppressed minority), and nationalist (high nationalist). The nationalist group was most likely to endorse rejecting Multiracial people as members of the Black community and also to endorse forcing a Black identity onto Multiracial people, whereas the integrationist group was least likely to make such endorsements. For participants in the nationalist (but not integrationist or undifferentiated) cluster, personal experiences of racism were related to endorsement of forcing a Black identity onto a Multiracial person. Findings suggest that Multiracial people might achieve the most identity affirmation and sense of community among Black people holding integrationist views.